2013
DOI: 10.1136/vetreccr.101036rep
|View full text |Cite
|
Sign up to set email alerts
|

Lipid infusion in the management of poisoning: a report of 6 canine cases

Abstract: Intravenous administration of lipid is a relatively new treatment in the management of toxicity from lipophilic compounds. It is used in human medicine in the treatment of toxicity from lipophilic local anaesthetics and cardiotoxic drugs and can result in dramatic improvement in clinical status. We present six cases of poisoning in dogs successfully treated with lipid infusion after ingestion of ivermectin (3), moxidectin (2) and baclofen (1). The dogs ranged in age from eight weeks to 14 years, and weighed 4–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…hypothermia, dyspnoea and respiratory arrest may occur (Campbell and Chapman, 2000;Wismer, 2004). Several cases of intoxication of dogs by baclofen following accidental ingestion of owner's tablets have been reported (Campbell and Chapman, 2000;Wismer, 2004;Scott et al, 2007;Torre et al, 2008;Khorzad et al, 2012;Bates et al, 2013;Caloni et al, 2014). In most cases, dogs develop severe clinical signs, often despite low dosage;~15% died (Campbell and Chapman, 2000).…”
Section: Muscle Relaxantsmentioning
confidence: 94%
See 2 more Smart Citations
“…hypothermia, dyspnoea and respiratory arrest may occur (Campbell and Chapman, 2000;Wismer, 2004). Several cases of intoxication of dogs by baclofen following accidental ingestion of owner's tablets have been reported (Campbell and Chapman, 2000;Wismer, 2004;Scott et al, 2007;Torre et al, 2008;Khorzad et al, 2012;Bates et al, 2013;Caloni et al, 2014). In most cases, dogs develop severe clinical signs, often despite low dosage;~15% died (Campbell and Chapman, 2000).…”
Section: Muscle Relaxantsmentioning
confidence: 94%
“…In most cases, dogs develop severe clinical signs, often despite low dosage;~15% died (Campbell and Chapman, 2000). Lethal doses for dogs have not been established, but the ASPCA APCC database has reported mortality in dogs at estimated doses of 8-16 mg/kg (Wismer, 2004), while Bates et al (2013) reported a case of poisoning in a dog that ingested a dose of 25 mg/kg. Death was also reported in an 8 week old dog that ingested a dose of 2.3 mg/kg (Table 5), indicating that the amount of baclofen ingested should not be used solely as a predictor of outcome (Khorzad et al, 2012).…”
Section: Muscle Relaxantsmentioning
confidence: 97%
See 1 more Smart Citation
“…ILE has also been used in a single case report of a dog with baclofen toxicosis and provided a rapid improvement in demeanour (Bates and others 2013). It must be noted that the use of ILE does not currently represent an appropriate first-line treatment option for baclofen toxicosis.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects reported in veterinary cases include pancreatitis (Gwaltney-Brant and Meadows 2012), hyperlipidaemia (Gwaltney-Brant and Meadows 2012), unilateral facial pruritus (Peacock and others 2015), extravasation with pain and local swelling (Bates and others 2013) and prolonged gross lipaemia (lasting more than 48 hours) and suspected corneal lipidosis (Seitz and Burkitt-Creedon 2016). The lipid also interferes with some laboratory analyses (Grunbaum and others 2015).…”
mentioning
confidence: 99%